2005
DOI: 10.1371/journal.pgen.0030106.eor
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific crossover distributions and variations in interference level along Arabidopsis thaliana chromosome 4

Abstract: In many species, sex-related differences in crossover (CO) rates have been described at chromosomal and regional levels. In this study, we determined the CO distribution along the entire Arabidopsis thaliana Chromosome 4 (18 Mb) in male and female meiosis, using high density genetic maps built on large backcross populations (44 markers, .1,300 plants). We observed dramatic differences between male and female map lengths that were calculated as 88 cM and 52 cM, respectively. This difference is remarkably parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
55
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 48 publications
12
55
0
Order By: Relevance
“…Thus, SC length differs significantly between male and female meiocytes in mouse and human, paralleling variations in the foci number of the protein MLH1, which is involved in the process of reciprocal recombination (Lynn et al 2002, Tease & Hulten 2004. Sex differences in SC length have also been reported in zebrafish, Dendrocoelum lacteum and others (for references see Kleckner et al 2003), and recently for chromosome 4 of A. thaliana (Drouaud et al 2007). On these grounds, one would expect that the SC length/DNA content in different plant species would also be positively related to their mean recombination rates (centimorgans per megabase, cM/Mb), and effectively this is found (see Table 3).…”
Section: Discussionmentioning
confidence: 85%
“…Thus, SC length differs significantly between male and female meiocytes in mouse and human, paralleling variations in the foci number of the protein MLH1, which is involved in the process of reciprocal recombination (Lynn et al 2002, Tease & Hulten 2004. Sex differences in SC length have also been reported in zebrafish, Dendrocoelum lacteum and others (for references see Kleckner et al 2003), and recently for chromosome 4 of A. thaliana (Drouaud et al 2007). On these grounds, one would expect that the SC length/DNA content in different plant species would also be positively related to their mean recombination rates (centimorgans per megabase, cM/Mb), and effectively this is found (see Table 3).…”
Section: Discussionmentioning
confidence: 85%
“…Crossover interference is a common phenomenon, but varies between sexes (Drouaud et al . ), among species (Segura et al . ) and even among chromosomes within a genome (Lian et al .…”
Section: Discussionmentioning
confidence: 99%
“…Both environmental (temperature and other stress conditions, Jain 1957) and genetic factors (genetic proximity of the parents, Modrich and Lahue 1996, presence of regulatory factors, Yandeau-Nelson et al 2006, sex, Moen et al 2004Drouaud et al 2007, gene density and percentage of GC residues, Schnable et al 1998;Paigen et al 2008) have been reported to affect recombination rate. On wheat, the crossover frequency increases from centromeres to the telomeres (Lukaszewski and Curtis 1993;Akhunov et al 2003;See et al 2006).…”
Section: Introductionmentioning
confidence: 99%